A new species of snake eel, Pisodonophis sangjuensis (Anguilliformes: Ophichthidae) from Korea - Ji, Hwan-Sung; Kim, Jin-Koo (Zootaxa, 2011)
A new snake eel, Pisodonophis sangjuensis, is described based on 24 specimens collected from the South Sea of Korea (water depth 5–100 m) between 2005 and 2010. This species is characterized by the following morphological features: fleshy protrusions before and behind the posterior nostril; 1–2 regular rows of conical teeth in both jaws, prevomer and vomer are slightly separated from each other; the origin of the dorsal fin above the middle of the pectoral fin; and the pectoral fin is rounded and not elongated. Pisodonophis sangjuensis is most similar to P. cancrivorus in morphology, but the two species differ in their teeth shape (conical in P. sangjuensis vs. granular in P. cancrivorus), and their numbers of vertebrae (143–153 vs. 153–164, respectively). Pisodonophis sangjuensis differs from P. boro in the origin of the dorsal fin (above the middle of the pectoral fin in P. sangjuensis vs. far behind the pectoral fin in P. boro), their numbers of vertebrae (143–153 vs. 170–177, respectively), and their teeth shape (conical in P. sangjuensis vs. granular in P. boro). Pisodonophis sangjuensis is also easily distinguishable morphologically from the remaining seven Pisodonophis spp. worldwide. Molecular analysis using mitochondrial DNA 12S rRNA sequences supported that P. sangjuensis is a new species because of the considerable genetic distance from what appears to be its most closely related species, P. cancrivorus (d=0.068).